A new record of the genus Adoretus Dejean, 1833 for Turkey: Adoretus (Adoretus) discolor (Falderman, 1835) (Coleoptera: Scarabaeidae: Rutelinae: Adoretini) - Özgen, İnanç; Keith, Denis; Kavak, Akif Emre (Baltic Institute of Coleopterology, 2018)
Adoretus (Adoretus) discolor (Falderman, 1835) is reported for the first time from Turkey. © 2018, Baltic Institute of Coleopterology. All rights reserved.
Keywords: Adoretus (adoretus) discolor; First record; Turkey